The Molecular and developmental insights into gonadogenesis and primordial germ cell migration in pacific white shrimp (Litopenaeus vannamei): A comprehensive review - Hananya, Ariel; Iman, Mohamad Nurul; Rifany, Ade; Kusuma, Satria Aji; Kurnia, Methodius Digna; Widodo, Rubiyanto; Efendy, Hendi Yanto; Jacinda, Adinda Kinasih; Akiyama, Dean Mikio; Laiman, Hendri (Genbinesia Journal of Biology, 2024)
The Pacific white shrimp, Litopenaeus vannamei, is a key species in global aquaculture, valued for its rapid growth and high market demand. Understanding the molecular mechanisms of gonadogenesis and primordial germ cell (PGC) migration in this species is vital for optimizing breeding programs. This review consolidates current knowledge on these processes, highlighting the role of the vasa gene as a germ cell marker. Vasa expression was tracked from fertilized eggs to juveniles aged four months, revealing the conserved DEAD-box helicase motif essential for germ cell development. Early detection of vasa messenger ribonucleic acid (mRNA) in developmental stages such as nauplius and zoea indicates its role in germ cell specification. By the post-larval stages, PGCs formed clusters associated with somatic gonadal precursor cells (SGPs), which support PGC migration and development. Quantitative polymerase chain reaction (qPCR) and reverse transcription PCR (RT-PCR) analyses demonstrated dynamic changes in vasa gene expression, suggesting critical windows for PGC proliferation and differentiation. Comparative studies with other species, such as Macrobrachium rosenbergii and Fenneropenaeus chinensis, emphasize the evolutionary conservation of germ cell development mechanisms. These insights are crucial for enhancing reproductive management and sustainability in shrimp farming, facilitating targeted interventions to improve breeding efficiency and hatchery success.